PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP KEBERLANJUTAN USAHA PEDAGANG PANGAN DI PASAR MODERN PASIR PENGARAIAN KABUPATEN ROKAN HULU - Syherli Syherli; Andi Afrizal; Ratna Dewi (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to analyze the influence of financial literacy and inclusion on the sustainability of food vendors' businesses at Pasir Pengaraian Modern Market, Rokan Hulu Regency. The survey research method uses a quantitative approach. The population in this study was 400 food vendors at Pasir Pengaraian Modern Market, while the sample was determined using a purposive sampling technique of 80 respondents. The research data were obtained by distributing questionnaires to respondents and analyzed using multiple linear regression. The discussion of the research results shows that financial literacy has a positive and significant effect on business sustainability, meaning that the better the ability of business actors to understand and manage finances, the greater the business's opportunity to survive and grow. Financial inclusion also has a positive and significant effect on business sustainability, indicating that access to formal financial services makes it easier for business actors to obtain capital and manage business transactions more effectively. The conclusion of this study is that financial literacy and financial inclusion, both partially and simultaneously, have a positive and significant effect on the sustainability of food vendors' businesses at Pasir Pengaraian Modern Market, Rokan Hulu Regency. Thus, improving financial literacy and expanding financial inclusion are important factors in supporting the sustainability of traders' businesses.